Primitive pelvic hydatid cysts - Perdomo, Roberto; Gardiol, Valdo C (Cirugía del Uruguay, 2020)
Three observations of single isolated hydatid cysts of the pelvis are presented, one of which spontaneously opened into the vagina. The national as well as the foreign literature relating to this subject is reviewed, and the observations on peritoneal and pelvian echinococcosis to be found in the files at the Hospital de Clínicas, and in the Surgical Clinic of Prof. Piquinela at the Pasteur Hospital ( both Montevideo) are studied as a whole. On these bases the thesis is advanced that pathogenically these cysts correspond to the homotopic primitive echinócoccosis. They may be recognized and distinguished from the secondary cysts of · peritoneal sowing by the surgeon through adequated exploration enabling him to uncover multiple differential characteristics in both forms. The autopsy facts as revealed by the statistics of the Telémaco Susini Institute of Buenos Aires, Argentina ( 18) are analyzed, to the effect of demonstrating overlapping with the surgical findings and the subsequent confirmation involved therein for the thesis set forth here, Also, the undamental characteristics o heterotopic primitive peritoneal echinococcosis seen in these pa¡fers are studied and a large group of facts emphasized which distinguish it sharply from the homotopic primitive pelvian cysts. Finally, the doctrinarian value of tlüs study is stqted, as also the practical use to be ma9-e of it for diagnosis, on the clinical side as also in the surgical exploration, for surgical tactics as well as for prognosis of the disease.